Ô nhiễm môi trường nước khu vực Rạch Tân Hóa - Lò gốm của TP.HCM - Nguyễn, Thị Lan (Đại học Quốc gia Hà Nội, 2014)
Tan Hoa - Lo gom creek is the one sewage system from a part of Tan Binh district 6 and 11 of Ho Chi Minh city. Some criteria of water quality were analysed as : DO<4mg/1, almost DO=0-mg/1; COD=200-500 mg/1; BOD5=200-300 mg/1; SS=100 - -200, in wet seaso SS=200-500 mg/1. Total Nitrogen=3-5 mg/1; Total Phosphor=0.2-0.5 mg/1. Comparing with environmental permitted standards, these criteria were higher than 2-3 times. Water resource has polluted due to waste of 4 big industrial zones with many factories as rubber, chemical, plastic, textile dying, paper, food, ec... and domestic waste from nearly a half of million of residents in the area.